How the legal system in Iceland works and what needs to be changed according to sexual violence victims - Lilja Hrönn Einarsdóttir 1992- (2022)
The aim of this study was to see how well the Icelandic legal system works according to victims of sexual abuse. Limited studies have been conducted about what it is that victims fear which can prevent them from pressing charges against their abuser. The research was conducted on Stígamót´s clients and through closed groups on Facebook with 257 participants. They all completed a questionnaire that included questions related to their abuse and opinion to the legal system. The answers indicated that for victims of sexual violence, opinion towards the legal system in Iceland was poor, as more than 80% of the participants said that the legal system worked "Very poorly". The question on what victims wanted to see changed in the process of pressing charges, the majority had a hard time to choose the most important, however, from seven issues, the one that had the highest score was the issue where they wanted to be able to have psychological assistance during and after the process. What was interesting in the current findings of the study was that the question where the victims were asked “Did sexual harassment or sexual violence have major or minor consequences for your quality of life?” more than half of the participants (72.5%) said it had “Very major” and “Major” consequences on their quality of life. This gives us the idea that something needs to be changed to increase the opinion of the Icelandic legal system from victims of sexual violence. Keywords: sexual abuse, legal system in Iceland, the Icelandic Parliament, sexual harassment, online sexual abuse, rape Útdráttur Markmið þessarar rannsóknar var að kanna hvaða viðhorf þolendur hafa til réttarkerfisins á Íslandi. Takmarkaðar rannsóknir hafa verið gerðar á því hvað það er sem brotaþolar óttast sem getur komið í veg fyrir að þau geti kært ofbeldismann sinn. Rannsóknin fór fram á skjólstæðingum Stígamóta og í gegnum lokaða hópa á Facebook. þátttakendur fylltu út spurningalista sem innihéldu spurningar sem tengdust ofbeldi þeirra og viðhorfi til ...